Tearing down the barriers to exercise after mastectomy: a qualitative inquiry to facilitate exercise among breast cancer survivors - Jiyong Byeon; Justin Y Jeon; Sujin Yeon; Ansuk Jeong; Jihee Min; Yong Jin Yoon; Jinmoo Heo; Chulwon Lee; Jeeye Kim; Seho Park; Seung Il Kim (BMJ Open)
Objective Proper exercise immediately after breast cancer surgery (BCS) may prevent unnecessary physical and psychological decline resulting from the surgery; however, patients’ attitude, barriers and facilitators for exercise during this period have not been studied. Hence, this study aims to explore the barriers and facilitators of exercise among patients with breast cancer through multiple interviews immediately after surgery through 4 weeks after BCS.Methods We conducted three in-depth interviews of 33 patients with breast cancer within 1 month after BCS.Results We identified 44 themes, 10 codes and 5 categories from interview results. Physical constraints and psychological resistance were identified as the barriers to exercise, while a sense of purpose and first-hand exercise experience were identified as the facilitators of exercise. By conducting the interviews over the course of 4 weeks after surgery, we monitored patterns of changes in barriers and facilitators over time. Overall, our analyses identified that professional intervention based on the time since surgery and the physical state after BCS is essential. The intervention would counteract the overwhelming psychological resistance in the early weeks by developing a sense of purpose in the later weeks.Conclusions We made suggestions for future research and exercise intervention programmes that can benefit breast cancer survivors based on the categories, codes and themes identified in this study.